2005
DOI: 10.1557/proc-0896-h01-05
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled Ordered Energetic Composites of CuO Nanorods and Nanowells and Al Nanoparticles with High Burn Rates

Abstract: Current approaches of mixing fuel and oxidizer nanoparticles or adding fuel nanoparticles to oxidizer gel lead to an overall reduced interfacial area of contact between them and thus, limit their burn rates severely. We have developed an approach of self-assembling fuel nanoparticles around an oxidizer matrix using a monofunctional polymer, poly(4)-vinyl pyridine (P4VP). The polymer has been used to accomplish binding of fuel and oxidizer in a molecularly engineered manner. We use composite of Al-nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Recently, self-assembly approaches were considered to prepare reactive nanocomposite materials starting with nanosized aluminum powder and functionalized nanosized oxide particles [106][107][108][109]. To produce ordered assemblies, metal particles were arranged around the exterior surface area of oxide nanorods or in the ordered pore structure of the mesoporous oxidizer particles in composites.…”
Section: Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, self-assembly approaches were considered to prepare reactive nanocomposite materials starting with nanosized aluminum powder and functionalized nanosized oxide particles [106][107][108][109]. To produce ordered assemblies, metal particles were arranged around the exterior surface area of oxide nanorods or in the ordered pore structure of the mesoporous oxidizer particles in composites.…”
Section: Self-assemblymentioning
confidence: 99%
“…The nanorods were prepared for these experiments using the surfactant-templating method. Al nanoparticles adhere to functionalized nanorods and these ''decorated'' nanorods become ordered within the material [107,108]. Such ordered structures are reported to produce higher flame speeds in small-scale laboratory evaluation tests compared to nanocomposite materials with the same compositions conventionally mixed using ultrasonicated suspension.…”
Section: Self-assemblymentioning
confidence: 99%
“…[1][2][3][4][5][6] The thermochemical properties of the materials used results in energy densities, for the most common mixtures, that are a factor of two or more higher on a volumetric basis than conventional organic based energetic (e.g., TNT or RDX). [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] The potential threats from biological-based weapons, such as those employing Bacillus anthracis, pose a significant challenge to global security. Of particular concern are spores of virulent bacteria that are highly stress resistant and cannot be completely killed by high-pressure processing (HPP), heat, or toxic chemicals such as iodophor.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers and ligands have also been employed as linkers to assemble fuel and oxidizer nanoparticles. Subramanium et al reported self-assembled fuel nanoparticles around an oxidizer matrix using poly(4)-vinyl pyridine (P4VP) [29,30]. Malchi et al employed charged ligands (COOHðCH 2 Þ 10 NMe þ 3 Cl À , SHðCH 2 Þ 10 COO À NMe þ 4 , etc.)…”
Section: Introductionmentioning
confidence: 99%